A cost effective foundry method for the preparation of structural grade discontinuously reinforced AIMCs - Kevorkijan, Varužan (Kovine zlitine tehnologije, 1998)
In this work, it was demonstrated that the wetting between ceramic particles and molten metal can be activated by exothermic interfacial reactions (e.g. Si+C ?$→$? SiC or 3?$TiO_2$?+3C+4Al ?$→$? 3TiC+2?$Al_2O_3$?). In this way, two methods of processing for introducing larger amounts of fine SiC particles into a Al alloy melt without rejection of the reinforcement, and without unwanted chemical reactions between the matrix and the reinforcement were developed. The introduction of fine (less than 6?$μ$?m) rounded-off SiC particles combined with a significant reduction in casting and extrusion defects caused by cost effective HIP treatment without encapsulation results in superior tensile properties. Moreover, in a defect-free composite, high aspect ratio reinforcements like SiC whiskers and platelets can be successfully used in order to improve the mechanical properties of final parts.
Keywords: livarstvo; kompoziti; aluminijeve zlitine; aluminium alloy; silicijev karbid; litje; mehanske lastnosti